Effects of Periodontal Treatment on CRP and Other Cellular Markers in Blood - Rojas González, Gisella (2025)
Periodontitis is a chronic inflammatory disease that affects public health worldwide. It has been related to microorganisms that trigger an inflammatory response that, in turn, produces a deterioration of the teeth’s supporting tissue. In recent years, studies have shown some similarity and association between periodontitis and atherosclerotic cardiovascular disease. The serum increases in C-reactive protein (CRP), fibrinogen, alpha-1 antitrypsin, moderate increase in leukocytes, increase in sedimentation rate and Von Willebrand factor antigen make it likely that there is a relationship between periodontal disease and other systemic conditions, specifically atherosclerotic disease. This study seeks to establish if there is any relationship between these values after phase II periodontal treatment in patients with periodontitis at the Faculty of Dentistry of the University of Costa Rica. The initial values are found in a previous publication (1).  In this second stage, the sample was reduced to 14 patients, of whom 57% presented metabolic compromise such as rheumatoid arthritis, arterial hypertension and diabetes mellitus, and 50% decreased PCR levels. As for the mean level of the total sample, in both stages of the study, PCR increased from 2.72 (SD: 2.25) to 5.36 (SD: 9.68). Of the patients who received periodontal treatment, 21.4% had low PCR levels (<1 mg/L), 50% medium (1-3 mg/L) and 28.6% high (>3 mg/L). There was no statistically significant difference in any of the variables analyzed for cholesterol, triglycerides and fibrinogen. Of the total number of patients in whom carotid ultrasound was performed, 52.4% were diagnosed as healthy, 33.3% had bulbar myointimal hyperplasia and 14.3% had atheromatous plaques. One of the participants died of myocardial infarction.  This study does not conclude that there is a relationship between periodontal disease and cellular markers, which are also found in atheromatous disease, but it can be affirmed that there is a probability that periodontal disease contributes to affect the metabolic condition of the patient.